The Role of Smallholder Farms in Food and Nutrition Security - Gomez y Paloma, Sergio; Riesgo, Laura; Louhichi, Kamel (Springer International Publishing : Imprint: Springer, 2020)
This open access book discusses the current role of smallholders in connection with food security and poverty reduction in developing countries. It addresses the opportunities they enjoy, and the constraints they face, by analysing the availability, access to and utilization of production factors. Due to the relevance of smallholder farms, enhancing their production capacities and economic and social resilience could produce positive impacts on food security and nutrition at a number of levels. In addition to the role of small farmers as food suppliers, the book considers their role as consumers and their level of nutrition security. It investigates the link between agriculture and nutrition in order to better understand how agriculture affects human health and dietary patterns. Given the importance of smallholdings, strategies to increase their productivity are essential to improving food and nutrition security, as well as food diversity.